Construction and Validation of a Machine Learning-Based Risk Prediction Model for Sleep Quality in Patients with OSA [Letter] - Wan H; Li Y; Xu F (Nature and Science of Sleep)
Hejia Wan,1 Yifan Li,2 Fei Xu3 1School of Nursing (Nursing School of Smart Healthcare Industry), Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 2Joint Institute of Management and Science University at Henan University of Chinese Medicine, Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 3School of Information Technology, Henan University of Chinese Medicine, Zhengzhou, People’s Republic of ChinaCorrespondence: Hejia Wan, Email 2022140071@hactcm.edu.cn